Market and Financial Analysis of General Islamic D-Class Hospital Establishment in Karangmojo Gunungkidul - Munifah Ashlihati; Firman Pribadi (Universitas Muhammadiyah Yogyakarta, 2019)
This study aims to analyze the market potential and financial feasibility of the General Islamic D-class Hospital establishment with a capacity of 100 beds in Karangmojo Gunungkidul. This was a quantitative descriptive design with a feasibility study approach. The research was conducted in Karangmojo Subdistrict, Gunungkidul. The data used are primary data through filling in questionnaires, then secondary data from the health department of Gunungkidul Regency. The results of market analysis showed that there were problems with hospital services faced by respondents in the form of slow service (33%), 39% of respondents felt doctors were lacking in providing explanations or education, most (96.76%) residents of Gunungkidul Regency were Moslems, The expectation of the community in the form of Islamic services is quite large (31%), it will be answered by professional and Islamic Islamic hospital services. The financial analysis obtained a value of 1) NPV = Rp.9,983,868,526.00; 2) IRR = 12.88%; 3) PI = 1.3193 times; 4) PP = 8 years 4 months; and ARR = 10.49%. Based on these results it can be concluded that In Karangmojo sub-district, Gunungkidul Regency, an Islamic hospital with 100 beds is feasible to be established from a review of the market and financial aspects.